Deducing the Role of Virus Genome-Derived PIWI-Associated RNAs in the Mosquito–Arbovirus Arms Race - Blair, Carol D. (Frontiers in Genetics, 2019)
The P-element-induced wimpy testis (PIWI)-associated RNA (piRNA) pathway is known for its role in the protection of genome integrity in the germline of Drosophila melanogaster by silencing transposable elements. The piRNAs that target transposons originate from piRNA clusters in transposon-rich regions of the Drosophila genome and are processed by three PIWI family proteins. In Aedes aegypti and Aedes albopictus mosquitoes, which are two of the most important vectors of arthropod-borne viruses (arboviruses), the number of PIWI family genes has expanded and some are expressed in somatic, as well as germline, tissues. These discoveries have led to active research to explore the possible expanded functional roles of the piRNA pathway in vector mosquitoes. Virus genome-derived piRNAs (which will be referred to as (virus name) vpiRNAs) have been demonstrated in Aedes spp. cultured cells and mosquitoes after infection by arthropod-borne alpha-, bunya-, and flaviviruses. However, although Culex quinquefasciatus also is an important arbovirus vector and has an expansion of PIWI family genes, vpiRNAs have seldom been documented in this genus after arbovirus infection. Generation of complementary DNA (cDNA) fragments from RNA genomes of alpha-, bunya-, and flaviviruses (viral-derived cDNAs, vDNAs) has been demonstrated in cultured Aedes spp. cells and mosquitoes, and endogenous viral elements (EVEs), cDNA fragments of non-retroviral RNA virus genomes, are found more abundantly in genomes of Ae. aegypti and Ae. albopictus than other vector mosquitoes. These observations have led to speculation that vDNAs are integrated into vector genomes to form EVEs, which serve as templates for the transcription of antiviral vpiRNA precursors. However, no EVEs derived from alphavirus genomes have been demonstrated in genomes of any vector mosquito. In addition, although EVEs have been shown to be a source of piRNAs, the preponderance of EVEs described in Aedes spp. vectors are more closely related to the genomes of persistently infecting insect-specific viruses than to acutely infecting arboviruses. Furthermore, the signature patterns of the “ping-pong” amplification cycle that maintains transposon-targeting piRNAs in Drosophila are also evident in alphavirus and bunyavirus vpiRNAs, but not in vpiRNAs of flaviviruses. These divergent observations have rendered deciphering the mechanism(s) of biogenesis and potential role of vpiRNAs in the mosquito–arbovirus arms race difficult, and the focus of this review will be to assemble major findings regarding vpiRNAs and antiviral immunity in the important arbovirus vectors from Aedes and Culex genera.